Applied reconfigurable computing : 12th International Symposium, ARC 2016 Mangaratiba, RJ, Brazil, March 22-24, 2016 Proceedings /: 12th International Symposium, ARC 2016 Mangaratiba, RJ, Brazil, March 22-24, 2016 Proceedings. (2016) - Unknown
No abstract available